Tembang dolanan as a medium for internalizing children's character values in the perspective of culture-based education - Seka Andrean; Sutiah (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Character education has become increasingly critical in addressing the moral and social challenges faced by children in the era of globalization and digital transformation, where cultural disconnection and declining social values are evident. This study aims to analyze tembang dolanan as a medium for internalizing children’s character values within the framework of culture-based education and to explain the mechanisms underlying this process. Using a qualitative approach with a systematic library research design, this study examines 42 scholarly sources related to cultural pedagogy, character education, and local wisdom. The analysis employs qualitative content analysis through coding, categorization, and thematic synthesis. The findings reveal that tembang dolanan functions as a culturally embedded pedagogical medium that facilitates the internalization of values such as religiosity, cooperation, discipline, responsibility, honesty, and creativity. This process occurs through four interconnected mechanisms: repetition, emotional engagement, social interaction, and experiential learning. Based on these findings, the study proposes the Cultural-Experiential Internalization Model (CEIM), which conceptualizes value internalization as a dynamic interaction between cultural input, learning processes, and character outcomes. The study concludes that tembang dolanan is not merely a cultural artifact but a relevant and adaptive educational resource that can support holistic character development when integrated into modern educational practices. This research contributes theoretically by offering an integrative conceptual model and practically by providing a foundation for developing culturally responsive character education strategies.